Development of Historical and Religious Tourism in Spatial Planning Towards the Utilization of Local Wisdom Potentials in Penyengat Island - Sutianto, Suwindar Agung; Sidabutar, Yuanita FD; Sinaga, M Ismael P (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The development of the tourism sector based on local wisdom, in supporting a sustainable tourism sector on Penyengat Island, especially historical and religious tourism, namely mosques, chair hills and tombs is urgently needed. The application of community-based tourism on Penyengat Island can be carried out in three stages, namely, the planning stage, the implementation stage and the evaluation stage. With the implementation of community-based tourism, the development of the tourism sector on Penyengat Island can run smoothly and still maintain the preservation of sustainable local wisdom, besides Therefore, with the development of a sustainable tourism sector, the lives of the people around it can be more prosperous and can increase income for the surrounding community. The results of the research show that the development of religious tourism on Penyengat Island as sustainable tourism is very feasible to develop, this is evidenced by the existence of a Regional Regulation concerning the Spatial Planning for the Riau Archipelago Province 2017-2037 as a legal basis as well as a commitment to sustainable development, community involvement in decision making and Management of religious tourism facilities and pre-facilities has existed before, such as tombs, mosques and historical buildings. Efforts to optimize the development of sustainable religious tourism are developing the concept of a cultural city, increasing regional security, improving infrastructure and drainage in some places, providing religious tourism attractions as new and more attractive additional attractions.